Electronic Government 13th IFIP WG 8.5 International Conference, EGOV 2014, Dublin, Ireland, September 1-3, 2014, Proceedings - Janssen, Marijn.; Janssen, Marijn.; Scholl, Hans Jochen.; Scholl, Hans Jochen.; Wimmer, Maria A.; Wimmer, Maria A.; Bannister, Frank Edward.; Bannister, Frank Edward. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2014)
This book constitutes the refereed proceedings of the 13th IFIP WG 8.5 International Conference on Electronic Government, EGOV 2014, held in Dublin, Ireland, in September 2014. The 26 revised full papers presented were carefully reviewed and selected from 70 submissions. The papers have been organized in the following topical sections: foundations; services and interoperability; policy and stakeholders; open data; and design and values.